CONDITORES URBIS ROMAE, LIWIUSZ I RZYMSKIE NUMIZMATY - Agata Aleksandra Kluczek (In Gremium. Studies in History, Culture and Politics, 2018)
In a description of a monument erected ad ficum Ruminalem by Ogulnii in 296 BC, T. Livius used the term conditores Urbis in reference to children who appear with the she-wolf. This is one of very rare examples of the use of this term by the historian in the Ab urbe condita. Such reference to the protagonists of the monument of the Ogulnii manifests an analogy in the content of the dedication of the monument (Marti invicto patri et aeternae urbis suae conditoribus), of which only the base with an inscription which dates back to the reign of emperor Maxentius (306–312) is preserved. These two monuments, the first of which was not preserved, and which is supposedly presented on the RRC 20 didrachm, the second of which (whose composition is merely a matter of conjecture) – constitute a framework for the occurrence of the presentation of the Lupa Romana group in Roman mintage. One may not rule out the possibility that these representations reflect the continuity of the tradition about the necessary role of both brothers, Remus and Romulus, in the establishment of Rome, conditio Urbis.